Vegetable oil-derived epoxy monomers and polymer blends: A comparative study with review - T. P. Schuman; R. Wang (eXPRESS Polymer Letters)
Glycidyl esters of epoxidized fatty acids derived from soybean oil (EGS) and linseed oil (EGL) have been synthesized to have higher oxirane content, more reactivity and lower viscosity than epoxidized soybean oil (ESO) or epoxidized linseed oil (ELO). The EGS and ESO, for comparison, were used neat and in blends with diglycidyl ether of bisphenol A (DGEBA). Thermosetting resins were fabricated with the epoxy monomers and either BF3 catalyst or anhydride. The curing behaviors, glass transition temperatures, crosslink densities and mechanical properties were tested. The results indicated that polymer glass transition temperatures were mostly a function of oxirane content with additional influence of glycidyl versus internal oxirane reactivity, pendant chain content, and chemical structure and presence of saturated components. EGS provided better compatibility with DGEBA, improved intermolecular crosslinking and glass transition temperature, and yielded mechanically stronger polymerized materials than materials obtained using ESO. Other benefits of the EGS resin blend systems were significantly reduced viscosities compared to either DGEBA or ESO-blended DGEBA counterparts. Therefore, EGS that is derived from renewable sources has improved potential for fabrication of structural and structurally complex epoxy composites, e.g., by vacuum-assisted resin transfer molding.